The Coase Theorem at Sixty - Medema, Steven G. (Journal of Economic Literature, 2020)
The Coase theorem is one of the most influential and controversial ideas to emerge from post–World War II economics. This article examines the theorem’s origins, diffusion, and the wide variety of uses to which it has been put by economists and others over the sixty years since Coase published “The Problem of Social Cost.” Along the way, we explore the ambiguity and controversy surrounding the theorem, develop a Coase theorem that is valid as a proposition in economic logic, and probe the implications of all of this for the use of the Coase theorem going forward. (JEL D23)